2021
DOI: 10.1021/acs.iecr.1c00603
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Dispersion and Selectivity of Chemical Reactions in the Inline Teethed High Shear Mixers

Abstract: The effects of various structural and operating parameters on liquid–liquid dispersion and selectivity of chemical reactions in inline single-row teethed high shear mixers (HSMs) were studied by a parallel competitive reaction system. The product distribution X S was applied to evaluate the mass transfer characteristics. The results show that X S decreases evidently at first in tandem with a slight increase as the rotor speed and flow rate rise. The results also indicate that the structural parameters of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…As shown in Figure a, there is a significant circulating flow in the center of the toothed rotor at N = 12 000 rpm, which enhances the collision between the two phases and thus the turbulence in the mixer. Such backflow appears stronger at higher rotor speeds and may contribute to the larger span of RT-ST. There is also an obvious circulation loop between the stator teeth.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…As shown in Figure a, there is a significant circulating flow in the center of the toothed rotor at N = 12 000 rpm, which enhances the collision between the two phases and thus the turbulence in the mixer. Such backflow appears stronger at higher rotor speeds and may contribute to the larger span of RT-ST. There is also an obvious circulation loop between the stator teeth.…”
Section: Resultsmentioning
confidence: 98%
“…The SIMPLE algorithm is used to solve pressure-linked equations . In all cases, the ratio of the time step to the rotor revolution period is 1:200 . The convergence criteria is all the total normalized residuals below 10 –4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Jasińska et al , suggested that the backmixing of the reaction solution into the feed area of the feed pipe increased X s under a high rotor tip speed. Thus, the aggravation of backmixing with increasing the rotor tip speed led to the deterioration of micromixing . Therefore, at a low rotor tip speed, the effect of increasing the turbulent kinetic energy dissipation rate on improving micromixing was greater than the side effect of increasing backmixing, consequently resulting in the improvement of the micromixing.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the aggravation of backmixing with increasing the rotor tip speed led to the deterioration of micromixing. 50 Therefore, at a low rotor tip speed, the effect of increasing the turbulent kinetic energy dissipation rate on improving micromixing was greater than the side effect of increasing backmixing, consequently resulting in the improvement of the micromixing. However, the side effect of backmixing became serious with increasing the rotor tip speed, which weakened this strengthening effect on the micromixing.…”
Section: Effect Of Acid Concentration and Rotor Tipmentioning
confidence: 97%